Clinically translatable quantitative molecular photoacoustic imaging with liposome-encapsulated ICG J-aggregates - Cayla A. Wood (Nature Portfolio, 2021)
Photoacoustic imaging is limited by a lack of contrast agents which can enable combined molecular and physiological imaging at depth. Here the authors address these limitations by developing and validating a contrast agent based on targeted liposomes loaded with J-aggregated indocyanine green dye.